The effect of natural and artificial grass on sprinting performance in young soccer players - Kanaras, V.; Metaxas, T. I.; Mandroukas, A.; Gissis, I.; Zafeiridis, A.; Riganas, C. S.; Manolopoulos, E.; Paschalis, V.; Vrabas, I. S. (American Journal of Sports Science, 2014)
The sprint performance on natural and artificial grass of 5th generation was assessed. Sixty eight young male soccer players, which were divided in two groups according to their age [children (n=36; 12.1±0.5y) and adolescents (n=32; 14.2±0.4y)], performed 30-m sprint tests with and without handling the ball on natural and artificial grass. The performance was recorded during 0-10m, 10-30m, and 0-30m running distances. It was found that children were significantly faster during 0-10m running distance on the artificial compared to natural grass when handling the ball while adolescents revealed no differences in sprint performance between the surfaces irrespectively of the ball condition. In running distances 10-30m and 0-30m, children were significant faster in the artificial compared to the natural grass either with or without ball, while the adolescents were significantly faster in the artificial grass only without handling the ball. Children run faster on artificial than natural grass while adolescent soccer players are faster in artificial grass when they do not have to handle the ball. It is clear that children should be more careful when play soccer on artificial grass because the ball is moving faster and greater skill is needed in order to avoid injuries.